1935
DOI: 10.1017/s0022172400032174
|View full text |Cite
|
Sign up to set email alerts
|

The Precipitation Reaction: Experiments on Multiple Zones

Abstract: 1. An antiserum containing antibodies for two unrelated antigens, crystalline egg albumin and crystalline horse serum albumin, has been prepared.2. In titrations of the antiserum against mixtures of these antigens it has been possible to produce a single zone or two zones of optimal particulation by varying the relative concentrations of the components in the antigenic mixtures. It is evident, therefore, that whilst (a) a single zone does not necessarily indicate a single antigen-antibody system, (b) multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1937
1937
1960
1960

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The method is based on the identification and correlation of a procedure optima occurring in the parallel titrations of a single antiserum against a mixed antigen and equivalent concentrations of physically or chemically prepared derivatives of it, supplemented by absorption of precipitins at individual and multiple oc procedure optima and retitration of the absorbed sera. In the first place antibody reactions whose optimal proportions are approximately equal, thus confirming the results of Taylor & Adair (1935). However, it seems clear that a single antigen-antibody reaction is manifested by a single zone of rapid particulation, and that the occurrence of two or more zones is due to the use of a mixed system.…”
Section: Conclusion Regarding the Anti-genic Constitution Of Horse Ssupporting
confidence: 76%
See 2 more Smart Citations
“…The method is based on the identification and correlation of a procedure optima occurring in the parallel titrations of a single antiserum against a mixed antigen and equivalent concentrations of physically or chemically prepared derivatives of it, supplemented by absorption of precipitins at individual and multiple oc procedure optima and retitration of the absorbed sera. In the first place antibody reactions whose optimal proportions are approximately equal, thus confirming the results of Taylor & Adair (1935). However, it seems clear that a single antigen-antibody reaction is manifested by a single zone of rapid particulation, and that the occurrence of two or more zones is due to the use of a mixed system.…”
Section: Conclusion Regarding the Anti-genic Constitution Of Horse Ssupporting
confidence: 76%
“…Taylor & Adair (1935) observed that the presence of another antigen-antibody system may cause changes of the proportions of an antigen and antiserum necessary for optimal particulation. Various physical and chemical methods are available for examining the homogeneity of a protein preparation and for defining and differentiating the constituent proteins of a mixture.…”
Section: Conclusion Regarding the Anti-genic Constitution Of Horse Smentioning
confidence: 99%
See 1 more Smart Citation
“…It will be seen that several of the systems show two clearly marked optimal reacting concentrations of antigen; this may be taken as evidence that, in these at least, more than one antigen-antibody reaction is taking place [cp. Dean et al 1935;Taylor & Adair, 1935;Goldsworthy & Rudd, 1935].…”
Section: M0-7mentioning
confidence: 99%